Richard Wright, Toni Morrison, and United States book clubs - Madigan, Mark J. (Acta neophilologica, 2004)
This essay focuses on the influence of commercial book clubs in the United States. It will examine the country's oldest commercial book club, the Book-of-the-Month Club (BOMC), Oprah's Book Club (OBC), which bears the name of its founder, television personality Oprah Winfrey, and their roles in the careers of two African-American authors, Richard Wright and Toni Morrison.
Keywords: afroameriška književnost; American literature; ameriška književnost; črnska književnost; knjižni klubi; Morrison, Toni, 1931-; Wright, Richard, 1908-1960; založništvo